Esilio e delirio: a partire dall’albero di lillà di María Zambrano (Altre Modernità, 2014)
Following the dreamlike symbolic image of lilac plant we will retrace the exile pathway of María Zambrano from Europe to Latin America and back again through inextricable memories of historical events, personal experiences and dreams. We will examine the existential and philosophical experience of exile as death and rebirth (desnacimento). Thanks to distance and separation from motherland, Zambrano could go through the radical dereliction that brought her to the inner solitude of the self. So that she could discover the function of delirium as a salvific force: the resistance of the past overcoming the ruins of history and opening to a new future. Therefore the misfortune of exile turns into good fortune and the outcasts become, in Zambrano’s words, “the beatified persons (los bienaventurados)”.